1992
DOI: 10.1177/019874299201700306
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Occupational Stress of Teachers of the Behaviorally Disordered: Sources, Effects, and Strategies for Coping

Abstract: A sample of 244 teachers of the behaviorally disordered completed the Pullis Inventory of Teacher Stress, a questionnaire regarding the sources, effects, and methods of coping with occupational stress. These teachers reported that school/setting factors, career issues, and workload variables were perceived as more stressful than direct contact with behaviorally disordered students. They indicated that exhaustion, frustration, and negative carryover to life outside the classroom were the most frequent effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 5 publications
1
32
0
4
Order By: Relevance
“…A partir dessa discussão, diversos estudos em diferentes países abordaram o tema como uma preocupante doença, principalmente na década de 90 (Benmansour, 1998;Burke, Greenglass, & Schwarzer, 1996;Chan & Hui, 1995;Dunham & Varma, 1998;Greenglass, Burke, & Konarski, 1998;Kyriacou, 2000;Pithers & Soden, 1998;Pullis, 1992;Travers & Cooper, 1996;Vandenberghe & Huberman, 1999 Sann (2003) destacam em seus estudos que a profissão de docência representa uma ocupação de elevado estresse atribuindo causas como a baixa motivação e comportamentos indisciplinares por parte dos alunos, excesso de tarefas a realizar, pressão de tempo e até mesmo conflitos com os colegas e a e a falta de organização escolar.…”
Section: Estresse Ocupacional Em Docentesunclassified
“…A partir dessa discussão, diversos estudos em diferentes países abordaram o tema como uma preocupante doença, principalmente na década de 90 (Benmansour, 1998;Burke, Greenglass, & Schwarzer, 1996;Chan & Hui, 1995;Dunham & Varma, 1998;Greenglass, Burke, & Konarski, 1998;Kyriacou, 2000;Pithers & Soden, 1998;Pullis, 1992;Travers & Cooper, 1996;Vandenberghe & Huberman, 1999 Sann (2003) destacam em seus estudos que a profissão de docência representa uma ocupação de elevado estresse atribuindo causas como a baixa motivação e comportamentos indisciplinares por parte dos alunos, excesso de tarefas a realizar, pressão de tempo e até mesmo conflitos com os colegas e a e a falta de organização escolar.…”
Section: Estresse Ocupacional Em Docentesunclassified
“…It was found that parental and administrative support is important in reducing burnout and encouraging motivation amongst special education teachers (Platt & Olson, 1990;Taylor & Salend, 1983;Zabel & Zabel, 2002). Other burnout predictors in this regard were: unclarity in role assignments, lack of colleague support, school conflicts (Crane & Iwanicki, 1986;Embich, 2001;Pullis, 1992), stress, unsupportive school climate (Miller, Brownell & Smith, 1999), advanced age in the workplace, difficult student population, inadequate home training (Banks & Necco, 1990;Zable & Zabel, 2001), and administrative failure in devising and implementing activities and plans (Cherniss, 1980(Cherniss, , 1988. Another study emphasized organizational characteristics as significant contributing factors to teacher burnout, such as school size, number of classrooms and the organizational climate (Sakharov & Farber, 1983).…”
Section: Learned Helplessness In the School Systemmentioning
confidence: 99%
“…The daunting tasks often overwhelm special education teachers, particularly beginners, and may become a primary factor in their decision to leave (Brownell & Smith, 1993). Pullis (1992) found that disruptive students and dealings with parents were rated the most stressful for teachers. It is very difficult for educators to perform effectively when their job is so stressful due to work related factors.…”
Section: Teacher Burnoutmentioning
confidence: 99%
“…Williams and Gersch (2004) found from interviewing teachers that the best direct ways to reduce burnout were utilizing time management skills, having clear and simple weekly plans, prioritizing and list making, With an average rating of2.74 for each situation, the participants' responses were between mildly and moderately stressful. When shown fifteen coping suggestions on the survey, the mean effectiveness rating was 2.51, which indicated that these ideas were mildly or temporarily effective and "pretty helpful" (Pullis, 1992). It is also important to note that some of the teachers stated that as a coping activity, they utilized drugs (including prescription) or drank alcohol to cope with the occupational stress.…”
Section: Teacher Burnout In Special Educationmentioning
confidence: 99%
See 1 more Smart Citation